2017
DOI: 10.5672/apunts.2014-0983.cat.(2017/4).130.03
|View full text |Cite
|
Sign up to set email alerts
|

Actituds cap al dopatge segons l’esport practicat pels joves

Abstract: En el mundo del deporte el ser humano ha buscado llegar a ser más rápido o más fuerte por lo que llega un momento en el que, en algunos casos, busca ayuda del dopaje, descrito como el uso de una sustancia o método

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…This study performed with 839 students shares similar features with the research carried out by Morente-Sánchez, Mateo-March & Zabala 2013, Yager & O'Dea (2014) and Morente-Sánchez & Zabala (2015). Just like in other studies that predate ours (Backhouse et al, 2013;Chan et al, 2015;Ruiz-Rico, Cachón, Valdivia & Zagalaz, 2014;Whitaker, Backhouse & Long, 2014), we found that attitudes are extremely important when taking the decision to use performance-enhancing drugs.…”
Section: Discussionsupporting
confidence: 83%
“…This study performed with 839 students shares similar features with the research carried out by Morente-Sánchez, Mateo-March & Zabala 2013, Yager & O'Dea (2014) and Morente-Sánchez & Zabala (2015). Just like in other studies that predate ours (Backhouse et al, 2013;Chan et al, 2015;Ruiz-Rico, Cachón, Valdivia & Zagalaz, 2014;Whitaker, Backhouse & Long, 2014), we found that attitudes are extremely important when taking the decision to use performance-enhancing drugs.…”
Section: Discussionsupporting
confidence: 83%